I must say [compact disc, unabridged] : my life as a humble comedy legend - Short, Martin, 1950-; Kamp, David (Harper Audio, 2014)
This deeply private man brings listeners into the circle of his family life, from raising his children to the legendary parties he and his wife hosted in their Los Angeles home. He recounts the pain of losing a brother and both parents by the time he was twenty, and of the devastating death of Nancy, his wife of thirty years, in 2010. Despite the hardships, Short's life has been full of laughter, and he remains perennially upbeat.